Youth self-formation and the ‘capacity to aspire’: the itinerant ‘schooled’ career of Fuzile Ali across post-apartheid space - Fataar, Aslam (Faculty of Education, University of the Free State, 2010)
This article is a narrative analysis of one young boy’s encounter with his schooling across the rural and urban landscape. It is set against the backdrop of the changing social reproductive context of education in South Africa in the democratic period. Based on in-depth qualitative interviews, the analysis probed the subjective basis on which this young boy encountered his various spatial terrains in order to establish his schooled career. The article employs the lenses of ‘aspiration’, ‘space’, and ‘technologies of self’ to present the argument that his ‘capacity to aspire’ has to be understood on the basis of his active self-formation and disciplining, accumulated across the itinerant spaces of his life. The aim of this article is to open a window onto how young people now go about navigating their educational aspirations in the light of their contingent life circumstances.
Keywords: Youth formation; Subjectivity; Aspiration; Schooling; Post-apartheid space